Swarming Behavior in Plant Roots - Ciszak, Marzena; Comparini, Diego; Mazzolai, Barbara; Baluska, Frantisek; Arecchi, F. Tito; Vicsek, Tamás; Mancuso, Stefano (PLOS ONE, 2012)
Interactions between individuals that are guided by simple rules can generate swarming behavior. Swarming behavior has been observed in many groups of organisms, including humans, and recent research has revealed that plants also demonstrate social behavior based on mutual interaction with other individuals. However, this behavior has not previously been analyzed in the context of swarming. Here, we show that roots can be influenced by their neighbors to induce a tendency to align the directions of their growth. In the apparently noisy patterns formed by growing roots, episodic alignments are observed as the roots grow close to each other. These events are incompatible with the statistics of purely random growth. We present experimental results and a theoretical model that describes the growth of maize roots in terms of swarming.